2020
DOI: 10.1029/2020jb019576
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Premagmatic Rifting in Shaping a Volcanic Continental Margin: An Example From the Eastern North American Margin

Abstract: Both magmatic and tectonic processes contribute to the formation of volcanic continental margins. Such margins are thought to undergo extension across a narrow zone of lithospheric thinning (~100 km). New observations based on existing and reprocessed data from the Eastern North American Margin contradict this hypothesis. With~64,000 km of 2-D seismic data tied to 40 wells combined with published refraction, deep reflection, receiver function, and onshore drilling efforts, we quantified along-strike variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 243 publications
(473 reference statements)
2
16
0
Order By: Relevance
“…We proposed that the difference in the lateral width of the transitional crust along the ENAM indicates that the crust experienced more localized extension in the south than in the north during the Mesozoic rifting. Recent studies (e.g., Greene et al, 2020;Lang et al, 2020) suggest that the crust in the southern ENAM had a stronger rheology than in more northern regions, which limited the crustal extension during rifting, supporting our hypothesis. In correspondence, the estimated volume of rifting-related magmatism is less in the southern ENAM than in the north (Greene et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We proposed that the difference in the lateral width of the transitional crust along the ENAM indicates that the crust experienced more localized extension in the south than in the north during the Mesozoic rifting. Recent studies (e.g., Greene et al, 2020;Lang et al, 2020) suggest that the crust in the southern ENAM had a stronger rheology than in more northern regions, which limited the crustal extension during rifting, supporting our hypothesis. In correspondence, the estimated volume of rifting-related magmatism is less in the southern ENAM than in the north (Greene et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Our model in the southern ENAM reveals that the Moho deepens from ∼15 km to ∼40–45 km over a horizontal distance of ∼70 km across the oceanic‐continental margin (Figures 3 and ). In comparison, the Moho depth increases gradually from ∼15 km landward to ∼45–50 km over a wide zone of ∼200 km beneath the continental shelf of southern New England (e.g., Lang et al., 2020; Pope et al., 2016). We proposed that the difference in the lateral width of the transitional crust along the ENAM indicates that the crust experienced more localized extension in the south than in the north during the Mesozoic rifting.…”
Section: Discussionmentioning
confidence: 99%
“…Larsen et al, 2008;Tiberi et al, 2019), previous studies have demonstrated that, across multiple scales, strain preferentially localises into relatively weaker areas with stronger bodies proving resistant to extension (e.g. Beniest et al, 2017;Lang et al, 2020;Wright et al, 2020;Samsu et al, 2021). However, less is known about how the characteristic geometry and development of fault networks and rift systems varies across these relatively 'strong' and 'weak' areas during extension.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth to note that the effect of increased magmatism with margin width does not exclude feedbacks from magmatism, which are not included in this study. For example, melt intrusion may weaken the lithosphere and ultimately limit the width of margins (Bastow et al., 2010; Buck, 2006; Keir et al., 2006; Lang et al., 2020). Such weakening may be particularly efficient at high mantle temperature when the melt production rate is high.…”
Section: Discussionmentioning
confidence: 99%